Social Responsibility in the Institutions of Higher Education from the Perspective of the Faculty Members at the Hashemite University - Al-Zyoud, Abd Al-Khaleq Muhammad (Journal of Educational and Psychological Sciences, 2020)
This study aimed to examine the reality of social responsibility practice among the academic leaders at the Hashemite University in light of some demographic variables (academic major, academic rank, post).To achieve the objective of the study, the researcher used a scale that was verified for its validity and reliability. The scale of social responsibility consisted of (23) items, divided into three dimensions: social responsibility towards the students, social responsibility towards the university, and social responsibility towards the community. The sample of the study consisted of (150) academic leaders at the Hashemite University in Jordan in the first semester of the academic year 2019/2020. The problem of the Study concern in several problems encountered by the faculty members at the Jordanian universities in terms of the practices of social responsibility. Also, this study was conducted in order to explore the level of social responsibility practiced through the academicians and faculty members at the Hashemite University. Methodology: This study is quantitative, in which data were collected through a questionnaire, which was designed and developed for the purposes of the present study. The results of the study showed that academic leaders at the Hashemite University exercise social responsibility of the three dimensions to a moderate degree from their perspective. In light of the study results, the researcher recommends a number of recommendations: conducting additional studies to explore the factors affecting the level of social responsibility, providing legislations and laws which may contribute to the development of the academic environment of the university that enhances the practices of social responsibility, provision of support for the faculty members at the Jordanian universities and solving the relevant problems they encounter.
Keywords: Social responsibility; Higher education; Faculty Members; Hashemite University